A High-Throughput Candida albicans Two-Hybrid System - Floris Schoeters (mSphere, 2018)
Candida albicans is a major fungal pathogen, and due to the rise of fungal infections and emerging resistance to the limited antifungals available, it is important to develop novel and more specific antifungals. Protein-protein interactions (PPIs) can be applied as very specific drug targets. However, because of the aberrant codon usage of C. albicans, the traditional yeast two-hybrid system in Saccharomyces cerevisiae is difficult to use, and only a limited number of PPIs have been described in C. albicans. To overcome this, a C. albicans two-hybrid (C2H) system was developed in 2010. The current work describes, for the first time, the application of the C2H system in a high-throughput setup. We hereby show the usefulness of the C2H system to investigate and detect PPIs in C. albicans, making it possible to further elucidate protein networks in C. albicans, which has the potential to lead to the development of novel antifungals which specifically disrupt PPIs important for virulence.Candida albicans is a human fungal pathogen that does not follow the universal codon usage, as it translates the CUG codon into serine rather than leucine. This makes it difficult to study protein-protein interactions using the standard yeast two-hybrid (Y2H) system in the model organism Saccharomyces cerevisiae. Due to the lack of adapted tools, only a small number of protein-protein interactions (PPIs) have been detected or studied using C. albicans-optimized tools despite the importance of PPIs to understand cell biology. However, with the sequencing of the whole genome of C. albicans, the availability of an ORFeome collection containing 5,099 open reading frames (ORFs) in Gateway-adapted donor vectors, and the creation of a Gateway-compatible C. albicans-specific two-hybrid (C2H) system, it became possible to study protein-protein interactions on a larger scale using C. albicans itself as the model organism. Erroneous translations are hereby eliminated compared to using the S. cerevisiae Y2H system. Here, we describe the technical adaptations and the first application of the C2H system for a high-throughput screen, thus making it possible to screen thousands of PPIs at once in C. albicans itself. This first, small-scale high-throughput screen, using Pho85 as a bait protein against 1,646 random prey proteins, yielded one interacting partner (Pcl5). The interaction found with the high-throughput setup was further confirmed with a low-throughput C2H experiment and with a coimmunoprecipitation (co-IP) experiment.